ChemInform Abstract: Transition‐Metal‐Catalyzed Chelation‐Assisted C—H Functionalization of Aromatic Substrates. Issue 25 (June 2016) - Zhao, Binlin; Shi, Zhuangzhi; Yuan, Yu
Abstract: Review: [40 refs.